TO ASSESS THE CORNEAL TOPOGRAPHY AND ENDOTHELIAL CELL DENSITY IN PATIENTS WITH PTERYGIUM - MUKHERJI, RITICA; SUNE, PRADEEP (International Journal of Psychosocial Rehabilitation, 2020)
Pterygium is a very common affliction amongst the working population of our country. A large number of studies have been conducted to enhance our knowledge regarding the pathos behind development of pterygium and its common associations. With the advent of newer modalities, like specular microscopy, we are at an advantage to study the influence of pterygium on the endothelial cell layer. To investigate the effects of pterygium on corneal endothelial cell density (ECD) and astigmatism in patients of pterygium and evaluate a correlation, if any, between ECD and corneal astigmatism in patients of pterygium. An observational cross-sectional study with 90 patients will be conducted in a hospital setting utilising data of fellow eyes as control. The area of cornea affected by pterygium will be compared to the endothelial cell density. Astigmatism in eyes with pterygium will be compared to decreased ECD using the appropriate statistical tests. than in the controls. The Pearson correlation test will be used to show correlation between pterygium size and ECD, if any. In addition, increase in astigmatism will be correlated with the endothelial cell density. Based on the few studies at hand we expect to find that pterygium will be linked to a fall in corneal ECD which may be correlated to increase in corneal astigmatism in patients with pterygium.